2023
DOI: 10.26434/chemrxiv-2023-1k3bw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trapping of Photoluminescent Kinetic Intermediates During High-Concentration Synthesis of Non-Emissive Metal-Organic Frameworks

Abstract: Metal-organic frameworks (MOFs) are porous, crystalline materials constructed from organic linkers and inorganic nodes with potential utility in gas separations, drug delivery, sensing, and catalysis. Small variations in MOF synthesis conditions can lead to a range of accessible frameworks with divergent chemical or photophysical properties. New meth-ods to controllably access phases with tailored properties would broaden the scope of MOFs that can be reliably prepared for specific applications. Herein, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 76 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…An interesting question is why Zr-MOFs tend to form the same phase at low and high linker concentrations, , whereas M 2 (dobdc) materials undergo a phase transition to a new kinetic product at high reaction concentrations. , We propose that Zr- and Hf-MOFs are especially well-suited for high-concentration synthesis because their M 6 nodes are robust and well-defined and, thus, strongly direct linker coordination into specific structures, even at high concentrations. In contrast, the metal centers that form the backbone of M 2 (dobdc) materials can engage in many different coordination environments with the linkers during MOF self-assembly.…”
Section: High-concentration Solvothermal Synthesismentioning
confidence: 81%
See 4 more Smart Citations
“…An interesting question is why Zr-MOFs tend to form the same phase at low and high linker concentrations, , whereas M 2 (dobdc) materials undergo a phase transition to a new kinetic product at high reaction concentrations. , We propose that Zr- and Hf-MOFs are especially well-suited for high-concentration synthesis because their M 6 nodes are robust and well-defined and, thus, strongly direct linker coordination into specific structures, even at high concentrations. In contrast, the metal centers that form the backbone of M 2 (dobdc) materials can engage in many different coordination environments with the linkers during MOF self-assembly.…”
Section: High-concentration Solvothermal Synthesismentioning
confidence: 81%
“…These frameworks are promising for gas storage and separations but are often difficult to produce on a gram scale, as they are typically synthesized under dilute (∼0.01 M) conditions in DMF/alcohol mixtures. We began by evaluating the synthesis of Mg 2 (dobdc) at linker concentrations varying from 0.01 to 1.50 M with stirring . PXRD analysis of the resulting materials confirmed that phase-pure Mg 2 (dobdc) was obtained at concentrations up to 0.05 M, but at 0.08 M, the MOF was contaminated with a previously unreported crystalline phase that we term CORN-MOF-1 (Mg).…”
Section: High-concentration Solvothermal Synthesismentioning
confidence: 97%
See 3 more Smart Citations